Impactos sociais das Fintechs : um estudo sociológico sobre como as instituições bancárias estão se reorganizando no mercado com o advento das Fintechs - Rodrigues, Jordana Cristina (2021)
The objective of this research was to investigate the Brazilian Banking Market, to identify and analyze, from the structural sociological approach of the markets, the relationship patterns between its main actors, the relationship between traditional Brazilian banking institutions and financial technology companies (Fintechs). The general hypothesis was inspired by Harrison White's theory of the social structure of markets. The result presented is based on secondary data from the reports made available quarterly by the four largest Brazilian banks listed on the stock exchange to their investors in the years 2014 to 2018. In these banks there were changes in their physical structures and changes in their performance, which we explain as responses to the performance of the Fintechs, such as the search to become increasingly digital. In other words, as suggested by the sociology of the markets, it seems that traditional banks have changed in the sense of approaching the model used by Fintechs. New research may support our findings, as it is an ongoing process of change.